2016
DOI: 10.1002/jclp.22363
|View full text |Cite
|
Sign up to set email alerts
|

On Belonging: The American Adolescent of Arab Descent

Abstract: Although American families of Arab origin come from 22 countries and from varied backgrounds and cultures, reports suggest that they suffer equally from acculturation stress, stereotyping, discrimination, and the reverberations of the aftermath of September 11 as well as global affairs. However, because children and adolescents from these families, particularly those who are newly arrived immigrants, tend to do well in school, they are rarely targeted by research or policy. This article uses the narratives of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The young and female participants may be living with their parents and influenced by their parents’ traditions, impeding their American acculturation. Khouri (2016) reported that as the second-generation children embrace both cultures, they may face conflicts with their parents on choice of peers especially if the peers were non-Arabs. Additionally, female participants may face intergenerational conflicts on social-related relationships, especially with the opposite gender and honor-related issues such as marriage and dating (Rasmi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The young and female participants may be living with their parents and influenced by their parents’ traditions, impeding their American acculturation. Khouri (2016) reported that as the second-generation children embrace both cultures, they may face conflicts with their parents on choice of peers especially if the peers were non-Arabs. Additionally, female participants may face intergenerational conflicts on social-related relationships, especially with the opposite gender and honor-related issues such as marriage and dating (Rasmi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study hold significant implications for understanding how interactions in school influence identity development for Arab heritage youth. The experiences that Arab American youth face in school may understandably increase levels of acculturative stress among Arab American adolescents (Aroian et al., 2014; Khouri, 2016). Consequently, these experiences impact mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Many of them suffer from isolation, as previously mentioned in knör's (2005) research on Germans coming back from South africa. Furthermore, research on the mental health of adolescents with migration experience report that this population suffers from emotional stress (Khouri, 2016). Studies of children and adolescents returning from Sweden to Finland (Vuorenkoscki et al 2001) have shown that the prevalence of mental illness, hospitalization and the transmission of infectious diseases was more frequent in this group than among the non-migratory population.…”
Section: Review Of Existing Researchmentioning
confidence: 99%